The emerging roles of TRIM21 in coordinating cancer metabolism, immunity and cancer treatment - Chen, Xintian; Cao, Menghan; Wang, Pengfei; Chu, Sufang; Li, Minle; Hou, Pingfu; Zheng, Junnian; Li, Zhongwei; Bai, Jin (Frontiers in Immunology, 2022)
Tripartite motif containing-21 (TRIM21), an E3 ubiquitin ligase, was initially found to be involved in antiviral responses and autoimmune diseases. Recently studies have reported that TRIM21 plays a dual role in cancer promoting and suppressing in the occurrence and development of various cancers. Despite the fact that TRIM21 has effects on multiple metabolic processes, inflammatory responses and the efficacy of tumor therapy, there has been no systematic review of these topics. Herein, we discuss the emerging role and function of TRIM21 in cancer metabolism, immunity, especially the immune response to inflammation associated with tumorigenesis, and also the cancer treatment, hoping to shine a light on the great potential of targeting TRIM21 as a therapeutic target.